Anthropometric measurements for detecting low birth weight - Kusharisupeni Kusharisupeni; Wahyu Kumia Y. Putra; Engkus Kusdinar Achmad (Paediatrica Indonesiana, 2013)
Background In several provinces of Eastern Indonesia, themajority of births take place at home (60%) and are assisted bytraditional birth attendants. Most of these newborns do not havetheir birth weight recorded, due to lack of available weighing scalesor lack of skill to perform the measurement, especially in ruralareas. As such, an early iden tification oflow birth weight cases isneeded to prevent infan t morbidity and mortality.Objective To assess anthropometric measurements including calf,chest, and h ead circumferences as a method of choice for detectinglow birth weight, as substitute for actual weighing.Methods This cross-sectional study was performed at BanjarBarn, South Kalimantan, Indonesia, from January to March 2012.Subjects were full term, singleton, and live-born infants duringthe study period, and obtained from private clinics by a purposivesampling procedure. Calf, chest, and h ead circumferences weremeasured to identify the most suitable substitute for birth weightusing Pearson's correlation, ROC, sensitivity, and specificity.Results In this study, a correlation was shown between birthweight and all anthropometric measurements. Optimal calf,chest, and head circumference cutoff points to identify low birthweight infants were 10.3 cm, 30. 7 cm, and 3 1.2 cm, respectively.The area under the curves (AUC) showed good accuracy for allmeasuremen t types. Calf circumference had the closest estimatedtrue prevalence to the true prevalence (8.52% and 8.6%, respectively)compared to the other measurement types.Conclusion Calf circumference is the most suitable measurementas a substitute for birth weight, due to its estimated trueprevalence.